PENINGKATAN KEMANDIRIAN UKM TUMPENG UPAKARA MELALUI MANAJEMEN KEUANGAN DAN PEMASARAN ONLINE DI BANJAR TATAG, SUKAWATI - Azis, Ita Sylvia Azita; Amlayasa, Anak Agung Bagus; Meitri, Ida Ayu Srie (JURNAL SEWAKA BHAKTI, 2025)
Tumpeng Upakara is a means of ceremonial equipment or offerings which are widely used as a complement to various types of offerings. The production process is still very simple, the process is done manually. Tumpeng ceremony produced by partners can last a long time, is clean white and not easily broken. The main problem faced by partners is related to the partner's very low knowledge regarding financial management, where partners' understanding is only limited to managing money, without thinking about how to manage finances to generate profits, and the results of business sales are often combined with personal money. partners also have problems from a marketing perspective. Marketing carried out by partners is still very traditional. The solutions given to partners' problems are (1) Providing knowledge to partners regarding the basic concepts of financial management which include: financial planning to good business financial management (2) Providing direct knowledge and practice regarding business financial control, classifying which expenses are for business and which one is for the family, so partners are able to grow with a healthy cash flow. (3) Providing training on using social media in promoting their business, so that the tumpeng ceremony business can be promoted more widely. The result of this community service activity is an increase in partners' knowledge regarding the concept of managing and controlling business finances.